A high-fidelity three-dimensional simulation method for evaluating passenger flow organization and facility layout at metro stations. (October 2017) - Hu, Mingwei
This research proposes a high-fidelity simulation method that integrates the strengths of microscopic pedestrian modeling and three-dimensional (3D) virtual reality (VR) for the evaluation of passenger flow organization and facility layout at metro stations. Passenger flow movements, with detailed spatial–temporal information of each agent, are modeled using agent-based micro-simulation. Simulation results are then imported into a 3D VR environment for the assessment of passenger flow organization and its interactions with facility layout. Focusing on the technical implementation of the method, we discuss in detail (1) finely resolved pedestrian simulation using AnyLogic; (2) bookkeeping of spatial positions of agents at the specific temporal intervals in XML format; and (3) interactive photo-realistic 3D visualization of pedestrian movements using UC-win/Road through its micro-simulation player plug-in, OpenMicroSim. Successfully applied to case studies of three major metro stations in Shenzhen China, this methodology is demonstrated to be capable of evaluating passenger flow organization through visual and quantitative analyses for improving facility layout design.